Accelerating into Immunization Agenda 2030 with momentum from China's successful COVID-19 vaccination campaign during dynamic COVID Zero - Lance E. Rodewald (BMC, 2023)
Abstract China's immunization programs conducted a unified, tightly coordinated COVID-19 vaccination campaign during the dynamic COVID Zero period that reached well over 90% of the population with vaccines having > 90% effectiveness against serious-to-fatal COVID-19. The campaign was eight times the size of the annual routine national immunization program, administering 3.4 billion doses of vaccines while monitoring vaccine coverage, acceptability, safety, and effectiveness. Every asset of the routine immunization program had to be strengthened and expanded to attain high coverage and reach hundreds of millions of adults who had not been vaccinated since childhood. Program strengthening and expansion were in directions aligned with the World Health Organization's Immunization Agenda 2030, which has a vision that "everyone, everywhere, at every age fully benefits from vaccines for good health and well-being" and requires reaching all children, adolescents, and adults with lifesaving vaccines. Momentum from this campaign should not be lost but should be invested into achieving what is possible with a properly resourced national immunization program that is now proven to be capable of reaching everyone in the world's largest country throughout the life course, and to do so with all vaccines recommended by the World Health Organization. Graphical Abstract